Evaluation of diatom Halamphora sp. and harpacticoid copepod Amphiascoides neglectus as live food for black tiger shrimp Penaeus monodon postlarvae - Baharuddin, Ninie Diana; Muthukhrisnan, Sarmila; de Cruz, Clement R.; Kassim, Zaleha; Hasnan, Hazwani Hanim; Abdullah, Mohd Ihsanudin; Khaw, Yam Sim; Tan, Hui Teng; Nazarudin, Muhammad Farhan; I., Natrah (Elsevier, 2024)
The present study investigated on the potential use of marine benthic diatom Halamphora sp. and harpacticoid copepod Amphiascoides neglectus enriched with Halamphora sp. on the growth, biochemical composition, water quality performance and disease tolerance of black tiger shrimp Penaeus monodon postlarvae culture. The introduction of Halamphora sp. and enriched harpacticoid copepod (EHC) as feed to the postlarvae increased the final weight gain (38.10 ±1.50 to 40.43 ±1.17 mg/individual), weight gain (1267.97 ±24.59 to 1321.09 ± 22.53%) and specific growth rate (9.34 ±0.22 to 9.47 ±0.26% day 1) significantly (p <0.05) compared to the commercial feed. The protein and lipid contents of the postlarvae fed with EHC (protein: 15.26 ±0.40% wet weight (WW); lipid: 1.91 ±0.07% WW) were significantly higher (p <0.05) compared to Halamphora sp. (protein: 13.66 ±0.51%WW; lipid: 1.70 ±0.01% WW) and the commercial feed. Moreover, the inclusion of Halamphora sp. and EHC into the postlarvae zero exchange water culture yielded lower nitrite (0.141 to 0.181 mg L 1), nitrate (3.15 to 8.50 mg L 1), orthophosphate (1.38 to 1.90 mg L 1), and total ammonia nitrogen (0.01 to 0.77 mg L 1) levels compared to the commercial feed. Finally, the incorporation of EHC into the diet also protected the postlarvae from the acute hepatopancreatic necrosis disease-causing Vibrio parahaemolyticus by demonstrating the highest survival rate (63.33%) of the postlarvae compared to Halamphora sp. (mortality rate: 63.33%) and commercial feed (mortality rate: 100%) treatments after 72 h of the challenge test. The current findings highlighted the great potential of using EHC as live food for better growth performance of P. monodon postlarvae as well as the protection against virulent shrimp pathogens.